Determining Long-Term Stability in Environmental Science (International Journal of Innovative Research in Computer Science & Technology, 2022)
A person's or a community's related  emissions is an indication of the number of energy needed to  produce their commodities. However, data shows that it only  lasts for a short period of time. There has been much criticism  of the assumptions behind the footprint assessments; here  authors offer more evidence that obvious economic  principles are not being fulfilled, because both the theory and  historical realities contradict the fundamental assumptions.  Indeed, writers contend that the trace arbitrarily refers to both  zero non-ideal ghgs as well as zero carbon dioxide emissions,  and national boundaries, making it difficult to extrapolate  from the average ecological footprint. Therefore, intensive  development may not be taken into account in the footprint  and comparisons of bio-capacity stand flawed. One may  make the case that, based on the principles of a footprint, the  planet supports significantly increased production, but  fundamental limitations such as land erosion do not resolve  the footprint. Last but not least, Environmental footprints are  obscured by a lack of linkage between land deterioration and  the environmental impact. Better environmental  measurements will address these issues in particular. Although, various research has been done earlier in this field  but there are vital opportunities of more research and  investigation in this domain in the future.
Keywords: Development; Environmental Science; Ecological Footprin; Greenhouse Gas; Sustainability